A Comparative Study on The Efficacy of A Commercial Prebiotic, Probiotic and Organic Acids in Improving the Performance of Broiler Chicken - Houshmand, Mohammad (2010)
Non antibiotics in the form of organic acids, prebiotics, probiotics and synbiotics have the potential to eliminate the usage of antibiotics in poultry feeding. Four experiments were conducted to establish the potencies and usage levels of commercial non antibiotics feed additives in poultry. Experiment 1 was a 4 × 2 factorial arrangement of four feed additive programs (a basal diet without any feed additive as control, basal diet added with organic acids, basal diet added with prebiotic and basal diet added with probiotic) with National Research Council (NRC) recommended or low (90 % of recommended) levels of energy. A total of 640 day-old male and female broiler chicks were randomly assigned to one of eight treatments, with four littered floor pens of 20 birds. Starter and finisher diets were fed from 1 to 21 and 22 to 42 d of age, respectively. Dietary level of other nutrients, housing and general management practices were same for all treatments. Dietary inclusion of additives had no significant effect on broilers performance, intestinal villus height, crypt depth, gut pH and dietary AME. Birds fed low energy diets were heavier (2447 g compared to 2390 g) but had inferior FCR (1.830 compared to 1.698) than those fed NRC recommended energy diets. However, protein digestibility was significantly higher for prebiotic (74.9 %) and organic acid (71.4 %) treatments compared to control (67.5 %). NRC recommended energy diets significantly increased AME and protein digestibility compared to low energy diets. No interaction was observed for measured parameters. In Experiment 2, a total of 288 day old male Cobb chicks were randomly assigned to a 2 × 4 factorial arrangement, with two levels of crude protein (NRC recommended or low) and four feed additive programs which were similar to experiment 1. Lowering dietary protein level, significantly decreased bird performance. Birds fed prebiotic supplemented diets had better FCR than control during 22-42 (1.882 vs 1.984) and 1-42 (1.769 vs 1.839) d of age. Also, supplementation with prebiotic resulted in longer duodenum villi compared to control treatment. All feed additives significantly increased antibody titers against Newcastle disease at 21 d of age. Experiment 3 was conducted using a 2 × 2 × 2 factorial arrangement with two levels of prebiotc (with or without), two levels of crude protein (NRC recommended or low level) and two levels of stocking density (normal or high). Protein level had significant effects on broiler performance. Supplementation with prebiotic had no significant effect on performance and other parameters. Birds reared at high density, had inferior finisher (22-42 d) and overall FCR (1-42 d) compared with birds housed at normal density. Significant interactions between protein levels and stocking density were observed for body weight gain and final body weight. Prebiotic, protein level and stocking density had no significant effect on spleen and bursa ratio weight. Protein level had no significant effect on antibody titer against Newcastle disease. However, normal density resulted in higher antibody titer (2.67) against Newcastle disease compared to high density (2.50). Stocking density had no significant effect on blood levels of glucose, cholesterol, corticosterone and heterophil to lymphocyte ratio. In Experiment 4, effects of different feed additives on performance, tibial dyschondroplasia (TD) incidence and tibia characteristics of male broilers fed low calcium diets were studied. A completely randomized design, with 6 treatments and 5 replicates of 5 chicks was used. Experimental treatments were: 1. Basal diet containing recommended level of calcium (1 %) as control treatment, 2. Low calcium (0.67 %) diet without any additive, 3. Low calcium diet added with probiotic, 4. Low calcium diet added with prebiotic, 5. Low calcium diet added with mixture of probiotic and prebiotic, 6. Low calcium diet added with organic acids. Different treatments had no effect on TD incidence. Feeding with low calcium diet negatively influenced not only broiler performance but also tibia characteristics. However, dietary inclusion of all feed additives had beneficial effects on above mentioned parameters. In conclusion, the results of current project indicated that prebiotic and organic acids improved protein digestibility. Supplementation with probiotic, prebiotic and organic acids resulted in better immunity as measured by higher antibody titers against Newcastle disease. When low calcium diets were fed, dietary inclusion of all feed additives had beneficial effects on broilers performance as well tibia characteristic. Under condition of this project, among different feed additives, prebiotic had the most beneficial effects on broilers.